The Thirst for Religion in Post-Enlightenment Age - Hafiz Muhammad Abdul Qayum (jihat-ul-islam, 2021)
Toynbee sees the vacuum of spirituality in western society, so, he says: "Life now is more secure than it was in the preceding age; but for this very reason it is also more dull. The benevolent action of efficient authoritarian governments has undesignedly created a spiritual vacuum in human souls." Allama Muhammad Iqbal narrates this spiritual vacuum in following words: "Surely, the present moment is one of great crisis in the history of modern culture. The modern world stands in need of biological renewal," Toynbee suggests that the predicaments confronting Western civilization in a postmodern age might be alleviated through a transfer of energy from economics to religion. Bell argues that a return to religion in Western civilization is required if postmodern problems arising from the existing ’shambles of appetite and self-interest and deconstruction of the moral circle which engirds mankind’ are to be resolved. "What is modern philosophy? Now modern philosophy has lost its importance in the postmodern age and presented the idea of the "end of philosophy". The most successful proponent of the end of ideology and indeed of history itself is Francis Fukuyama. His article "The End of History"? I think Islam and its teachings are better alternative to liberal capitalism. Rorty says that a modern ideology like liberal democracy has lost its justification: Similarly Merold Westphal writes that announcement by Nietzsche that "God has died," has been "replaced" by end of philosophy in postmodern era. "Postmodernism replaces Nietzsche’s announcement of the death of God with an announcement of the end of philosophy." Max Charlesworth says that Heidegger and Derrida strongly suggest that there is a space for God and religion in postmodern age. W. Montgomery Watt has desired for the Oneness of God to get rid of the Trinitarian faith of Christianity which is under arrest in Greek philosophy. According to the statistical data on religious adherents. Islam is only growing religion in the modern world. Keeping in view the objective facts of the postmodern world, Watt in an interview, answering the question that what can Islam teaches to Christianity says: "Speaking personally, it has taught me to think more deeply about the Oneness of God. I am not happy with the traditional Trinitarian Christian formulation of God comprising three "Person’-Father, Son and Holy Spirit.